Decentralized Tax Revenue, Institutional Complementarity and Economic Growth: A Time Series Analysis of Pakistan - Shahid, Muhammad; Kalim, Rukhsana (International Journal of Economics and Financial Issues, 2020)
Fiscal decentralization is one of the major policy variables to attain economic efficiency. The present study examines the impact of decentralized taxes on the economic growth of Pakistan from 1976 to 2018. For examining the stationarity of variables, Kwiatkowski-Phillips-Schmidt-Shin (KPSS) and Ng-Perron unit root Tests are used. Autoregressive Distributed Lag Approach (ARDL) is used for co-integration among the variables of the model. The results suggest that decentralized tax revenue i.e. income tax decentralization and sales tax revenue with political institutions have growth promoting impact on the economy of Pakistan. With strong institutions, provincial governments can give better results while transferring responsibility of collecting income tax from federal to provincial level. Keywords: Stationarity, Income tax and sales tax, decentralization, political institutions, economic growth. JEL Classifications: H2, H77, O1 DOI: https://doi.org/10.32479/ijefi.9724